2017
DOI: 10.1136/bmjsem-2017-000290
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy and physical activity: a cross-sectional survey exploring physical activity promotion, knowledge of physical activity guidelines and the physical activity habits of UK physiotherapists

Abstract: ObjectivePhysical inactivity is a public health priority and embedding promotion of physical activity (PA) within healthcare systems is an important lever for change. Many factors influence PA promotion in routine healthcare practice; these include the PA habits of healthcare professionals and also their knowledge of the PA guidelines. Little is known about the extent to which PA is currently promoted in physiotherapy practice or the factors that influence it.MethodsFollowing ethical approval, a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 33 publications
10
78
1
4
Order By: Relevance
“…In line with previous studies in which physical therapists indicated the use of different behavioural change techniques and interventions to promote PA [15,17,19,33] However, exercise therapists in our study rarely referred to scientific theories of behavioural change in their argumentation patterns for PAP. References to existing concepts of theory-based intervention for PAP in exercise therapy [9,30,35,36] were also rarely made by the therapists.…”
Section: Discussionsupporting
confidence: 87%
“…In line with previous studies in which physical therapists indicated the use of different behavioural change techniques and interventions to promote PA [15,17,19,33] However, exercise therapists in our study rarely referred to scientific theories of behavioural change in their argumentation patterns for PAP. References to existing concepts of theory-based intervention for PAP in exercise therapy [9,30,35,36] were also rarely made by the therapists.…”
Section: Discussionsupporting
confidence: 87%
“…In line with previous studies in which physical therapists indicated the use of different behavioural change techniques and interventions to promote PA [15,17,19,32] However, exercise therapists in our study rarely referred to scientific theories of behavioural change in their argumentation patterns for PAP. References to existing concepts of theory-based intervention for PAP in exercise therapy [9,29,34,35] were also rarely made by the therapists.…”
Section: Discussionsupporting
confidence: 87%
“…For practitioners, greater impact may be achieved by developing an accessible physical activity framework, which includes contemporary knowledge on guideline recommendations, thus encouraging further active promotion within the chiropractic setting. 60…”
Section: Discussionmentioning
confidence: 99%